Herbal Extract Incorporated Nanofiber Fabricated by an Electrospinning Technique and its Application to Antimicrobial Air Filtration - Choi, Jeongan; Yang, Byeong Joon; Bae, Gwi-Nam; Jung, Jae Hee (American Chemical Society, 2015)
Recently, with the increased attention to indoor air quality, antimicrobial air filtration techniques have been studied widely to inactivate hazardous airborne microorganisms effectively. In this study, we demonstrate herbal extract incorporated (HEI) nanofibers synthesized by an electrospinning technique and their application to antimicrobial air filtration. As an antimicrobial herbal material, an ethanolic extract of Sophora flavescens, which exhibits great antibacterial activity against pathogens, was mixed with the polymer solution for the electrospinning process. We measured various characteristics of the synthesized HEI nanofibers, such as fiber morphology, fiber size distribution, and thermal stability. For application of the electrospun HEI nanofibers, we made highly effective air filters with 99.99% filtration efficiency and 99.98% antimicrobial activity against Staphylococcus epidermidis. The pressure drop across the HEI nanofiber air filter was 4.75 mmH(2)O at a face air velocity of 1.79 cm/s. These results will facilitate the implementation of electrospun HEI nanofiber techniques to control air quality and protect against hazardous airborne microorganisms.
Keywords: SOPHORA-FLAVESCENS NANOPARTICLES; NATURAL-PRODUCT NANOPARTICLES; SILVER NANOPARTICLES; CARBON NANOTUBES; COPPER NANOPARTICLES; INDUCED INACTIVATION; SOPHORAFLAVANONE-G; TEA TREE; BIOAEROSOLS; FILTERS